Religião e conexão eleitoral: um estudo sobre a frente parlamentar evangélica da câmara de vereadores do Recife - Bispo, Hugo Cavalcanti (2020)
Our research analyses the performance of the Evangelical Parliamentary Front (EPF) of Recife’s City Council during the 16º legislature (2013 – 2016). Its declared goal was to defend the values of the Christianity and of the family and combat the use of drugs. Our research question was: what influence did religion have on the mandate of the members of the front? Therefore, under the theoretical perspective of electoral connection, we have analyzed the bills and the parliamentary amendments proposed by its representatives, in order to classify their legislative production, identify the importance of their declared flagships and observe how much of their bills became public policy. Furthermore, it was analyzed the position takings carried out by the councillors in plenary. The results indicated moderate commitment to the flagships of the EPF, besides an unequal performance by its members.